2018
DOI: 10.31234/osf.io/kx2qf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of Social Dominance on prejudice towards North-African minorities: Evidence for the role of Social Representation of Secularism as a Legitimizing Myth.

Abstract: Secularism in France is both a state principle and a cultural construct, that enforces a State neutrality towards religion. Recent studies have demonstrated the emergence of a lay conception called ‘New Secularism’ (NS) that is used to legitimize expression of prejudice towards North African minorities. However, none have been able to yet demonstrate links between NS and Social Dominance Orientation (SDO), which would further corroborate those beliefs’ role as prejudice justification. Using Social Representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Whereas, low-SDO individuals are more likely to favor egalitarian ideologies, such as multiculturalism (serving a HA-LM function), and this endorsement negatively predicts prejudice ( Levin et al, 2012 ; Guimond et al, 2013 ; Rattan and Ambady, 2013 ). Thus, in light of SDT, an emerging hypothesis is that the two Laïcité norms represent cultural legitimizing myths in France ( Roebroeck and Guimond, 2017 ; Troian et al, 2018 ). Hence, depending on their SDO Level, French citizens will either slant toward the egalitarian Historic Laïcité to enable its HA-LM function, or toward the assimilationist New Laïcité to capitalize on its HE-LM function.…”
Section: From the Two Laïcité Norms To Prejudice: An Indirect-endorsementioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, low-SDO individuals are more likely to favor egalitarian ideologies, such as multiculturalism (serving a HA-LM function), and this endorsement negatively predicts prejudice ( Levin et al, 2012 ; Guimond et al, 2013 ; Rattan and Ambady, 2013 ). Thus, in light of SDT, an emerging hypothesis is that the two Laïcité norms represent cultural legitimizing myths in France ( Roebroeck and Guimond, 2017 ; Troian et al, 2018 ). Hence, depending on their SDO Level, French citizens will either slant toward the egalitarian Historic Laïcité to enable its HA-LM function, or toward the assimilationist New Laïcité to capitalize on its HE-LM function.…”
Section: From the Two Laïcité Norms To Prejudice: An Indirect-endorsementioning
confidence: 99%
“…Concerning the New Laïcité, SDO does not predict its endorsement ( Kamiejski et al, 2012 ) or weakly so (below 0.20; Roebroeck and Guimond, 2017 , 2018 ), while its endorsement is indeed positively correlated to prejudice. This unanticipated absence of a SDO-New Laïcité link led Troian et al (2018) to suspect measurement issues in past studies. By developing their own New Laïcité measurement tool, they uncovered the predicted mediation: They found that higher SDO levels are associated with stronger New Laïcité endorsement which, in turn, predicts a higher level of prejudice.…”
Section: From the Two Laïcité Norms To Prejudice: An Indirect-endorsementioning
confidence: 99%
See 1 more Smart Citation
“…In France, social scientists typically eschew the term Islamophobia for precisely this reason, because it is seen as ill-defined, too often extending to describe disparate phenomenon ranging from racism to anti-terrorism ( Shryock, 2010 ). Perhaps not coincidentally, an aversion to the label “Islamophobia” coincides with efforts to directly restrict and control religious expression, beyond a general state secularism, a phenomenon referred to as new secularism ( Troian et al, 2018 ). In studies conducted in France in the aftermath of terrorist attacks, new secularism (example item, “ Some religions go against secularism,” emphasis added) can partially explain the relationship between social dominance orientation and prejudice against North Africans ( Troian et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps not coincidentally, an aversion to the label “Islamophobia” coincides with efforts to directly restrict and control religious expression, beyond a general state secularism, a phenomenon referred to as new secularism ( Troian et al, 2018 ). In studies conducted in France in the aftermath of terrorist attacks, new secularism (example item, “ Some religions go against secularism,” emphasis added) can partially explain the relationship between social dominance orientation and prejudice against North Africans ( Troian et al, 2018 ). These studies demonstrate how these dimensions of perceiving Muslims—which correspond to subtyping—are empirically distinct but politically entwined because these ways of talking and thinking about Muslims occur in tandem.…”
Section: Introductionmentioning
confidence: 99%